A Highly Rare Cause of Lumbar Spondylodiscitis with Epidural Abscess: Actinomyces israelii - Mahir Kapmaz; İsmail Gülşen; Naciye Kış; Seniha Başaran; Lütfiye Öksüz; Nezahat Gürler (Case Reports in Infectious Diseases)
Actinomyces species may lead to slowly progressive infection of almost any site once mucosal breakdown exists; hence, it has the name “great pretender.” Its diagnosis may be unthinkable unless proper cultures/histologies are taken. We describe a patient with lumbar spondylodiscitis and epidural abscess. This is an exceptional another disease by actinomycosis.